2021
DOI: 10.1101/2021.01.21.427563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Publication practices during the COVID-19 pandemic: Biomedical preprints and peer-reviewed literature

Abstract: The coronavirus pandemic introduced many changes to our society, and deeply affected the established in biomedical sciences publication practices. In this article, we present a comprehensive study of the changes in scholarly publication landscape for biomedical sciences during the COVID-19 pandemic, with special emphasis on preprints posted on bioRxiv and medRxiv servers. We observe the emergence of a new category of preprint authors working in the fields of immunology, microbiology, infectious diseases, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Preprints, for example, are becoming increasingly popular option for authors, as they provide visibility, feedback from peers, and greater attention for the final published version (Baffy et al, 2020;Fu & Hughey, 2019;Pagliaro, 2021;Preprints, 2021;Serghiou & Ioannidis, 2018). Preprints have played a major role in disseminating research findings on the COVID-19 pandemic (Sevryugina & Dicks, 2021).…”
Section: Preprints Vs Journalsmentioning
confidence: 99%
“…Preprints, for example, are becoming increasingly popular option for authors, as they provide visibility, feedback from peers, and greater attention for the final published version (Baffy et al, 2020;Fu & Hughey, 2019;Pagliaro, 2021;Preprints, 2021;Serghiou & Ioannidis, 2018). Preprints have played a major role in disseminating research findings on the COVID-19 pandemic (Sevryugina & Dicks, 2021).…”
Section: Preprints Vs Journalsmentioning
confidence: 99%
“… 21 A separate assessment of preprints in the first four months of 2020 found that the average time for a preprint to become a published paper was 63 days. 22 Another study found that peer-reviewed COVID-19 papers took an average of 83.8 days between submission and publication, relative to 199.7 days for non-COVID-19 papers and 201.7 days for pre-COVID-19 papers. 23 …”
Section: Preprints In the Covid-19 Era: Ethical Challengesmentioning
confidence: 99%
“…The low conversion of preprints to journal articles is consistent with other research on preprints during COVID-19. [30,31] The time to journal publication for preprinted trials requires additional follow-up and consideration alongside emerging evidence on the relationship between preprints and the peer-reviewed COVID-19 academic literature. [11] .…”
Section: Research In Contextmentioning
confidence: 99%